Bankruptcy Settlement of Baitul Maal Wa Tamwil in Yogyakarta: An Islamic Law Perspective - Muh. Yusron Rusdiyono; Amir Mu'allim (Millah: Journal of Religious Studies, 2022)
This research analyzes the bankruptcy settlement of baitul maal wa tamwil using two perspectives: positive law applied in Indonesia and Islamic law. The research method used in discussing the problem was by conducting normative-juridical research with the maqashid of the sharia approach. The results showed that the leading cause of the bankruptcy of baitul maal wa tamwil in the Special Region of Yogyakarta was the existence of several general problems internally, which included limitations in material law, human resources, legal culture, and supporting infrastructure. Another factor that also affects bankruptcy is the weakness of the internal control system by the Sharia Supervisory Board and externally by the Agency of Cooperative. The ideal settlement of the bankruptcy of baitul maal wa tamwil is the arrangement of a new bankruptcy regulation to accommodate the various rules still spread in several existing laws and regulations.